PENGARUH KOMPETENSI PROFESIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN KEPALA SEKOLAH - Ibrohim, 13.5202.0120 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the role of the Leadership Principal Moderating Effect of Professional Competence and Motivation for Primary Teachers performance throughout the District Talun Pekalongan. In this study population all primary school teachers in the district Talun civil servants, whereas samples taken as many as 136 people as respondents with purposive sampling technique. Measurements using a Likert scale of 5 (five) alternative answers. Test instruments used are validity and reliability. While the test model used is the coefficient of determination and F test (goodnes of Fit). Test this hypothesis using regression analysis. Based on the results of the study can be summarized as follows: (i) Professional Competence positive and significant impact on teacher performance, (ii) Work Motivation positive and significant impact on teacher performance, (iii) Leadership Principal has no effect on teacher performance, (iv) Leadership Principal does not moderate the influence of professional competence of the teacher performance, (v) Leadership Principal Work Discipline does not moderate influence on Teacher Performance.Keywords: Professional Competence, Motivation, Leadership of Headmaster and Performance Teachers.